FATIGUE LIFE SIMULATION OF CONCRETE PAVEMENT STRUCTURE WITH NANOMATERIAL CONCRETE SLAB IN TROPICAL ENVIRONMENT - Care, Frisky Ridwan Aldila Melania; Irfanto, Ryobi (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2025)
Recent studies on nanomaterial concrete in Indonesia have demonstrated improvements in mechanical properties, particularly in the context of fatigue life for concrete road pavements. While traditional designs focus primarily on traffic axle loads, curling stress from temperature differentials also plays a significant role. Previous research using 3D finite element analysis (FEA) software, such as EverFE2.26, showed that the tensile and curling stresses matched those calculated by established methods like Westergaard and Bradbury. This research uses a mechanistic approach and 3D finite element analysis (FEA) software for simulations. A literature review gathered data on the mechanical properties of nanomaterial concrete. After inputting all required parameters, EverFE2.26 performed a stress analysis, allowing for the calculation of concrete pavement fatigue life. The simulation showed that temperature differential greatly impacts the fatigue life of concrete pavements in tropical environments like Indonesia. Nevertheless, nanomaterial concrete could be a promising option to reduce those impacts if its strength can be further improved